Sarcopenia among Genders in Type 2 Diabetes Mellitus Patients Using Different Formulas of Bioimpedance Analysis - ÇİFÇİLİ, SALİHA SERAP (COLL PHYSICIANS & SURGEONS PAKISTAN, 2018)
Objective: To assess the frequency of sarcopema in type 2 diabetes mellitus (DM) patients using different formulas of bioimpedance analysis (BIA) Study Design: Cross-sectional study. Place and Duration of Study: Obesity Clinic, Kartal Dr. Lutfi Kirdar Training and Research Hospital, Istanbul, Turkey, between March and June 2015. Methodology: The present study included DM patients at >= 18 years of age with BMI >= 30 kg/m(2). BIA measurements consisted of body weight, height, total muscle mass and sum of the muscle masses of the four limbs (ALM). Skeletal muscle index, total muscle index, skeletal muscle percentage, total muscle percentage, and ALM/BMI were used for muscle-related analyses. The data were presented as frequency, mean +/- standard deviation, and percentage Student t-test was used to compare differences between two independent groups. Results: A total of 295 DM patients were enrolled in the study, of whom 176 (59.66%) were females, 119 (40.34%) were males, 47 (15.93%) were over the age of 65 years, and the mean age was 53.39 +/- 10.39 years. Sarcopenia was determined in 40 males (33.61%) by body muscle ratio, in 15 males (12.60%) by ALM/BMI ratio, and in one male participant (0.84%) by skeletal muscle index. Among female participants, while sarcopenia was determined in 61 (34.65%) by body muscle ratio and in 1 (0.56%) by ALM/BMI ratio, no sarcopenia case was detected using skeletal muscle index. Conclusion: The frequency of sarcopenia in obese diabetic patients is found to be lower when skeletal muscle index and ALM/BMI ratio is used, but higher with body muscle ratio.
Keywords: Diabetes mellitus type 2; Sarcopenia; Obesity; Muscle weakness; SKELETAL-MUSCLE MASS; KOREAN POPULATION; PHYSICAL-DISABILITY; INSULIN-RESISTANCE; METABOLIC SYNDROME; NATIONAL-HEALTH; PREVALENCE; OBESITY; ADULTS; WOMEN